2011
DOI: 10.4314/ijbcs.v5i1.68106
|View full text |Cite
|
Sign up to set email alerts
|

Effet des cordons pierreux sur l’activité biologique d’un sol ferrugineux tropical lessivé (Province du Kouritenga au Burkina Faso)

Abstract: Afin de comprendre le mécanisme de restauration des sols dégradés, l'effet des cordons pierreux sur la macrofaune (méthode TSBF), les teneurs en carbone organique (méthode de Walkley et Black) et en azote (Kjeldahl) et sur l'activité biologique du sol (mesure du dégagement du CO 2) a été évalué. Les résultats montrent que les cordons pierreux ont un effet positif sur la macrofaune du sol : en effet, 208 individus ont été recensés dans le champ aménagé en cordons pierreux, contre seulement 32 individus dans le … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
1
12
0
5
Order By: Relevance
“…As a result, agroecological practices showed a better distribution of soil microorganisms. For those indexes, our result was conformed to Doamba et al (2011). Campbell et al (2008) showed in a similar experiment that agricultural land-use practices could have significant effects of the same order as ours in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a result, agroecological practices showed a better distribution of soil microorganisms. For those indexes, our result was conformed to Doamba et al (2011). Campbell et al (2008) showed in a similar experiment that agricultural land-use practices could have significant effects of the same order as ours in this study.…”
Section: Discussionsupporting
confidence: 90%
“…All this contributes to creating favorable conditions for the development of soil microorganisms, hence shown by the strong biological activity recorded at these soils relative to the absolute witness. There is strong evidence that stony cords would enhance the potential for mineralization of agricultural soils (Doamba et al, 2011). However the stone-rows alone could not lead to a depletion of the soil in organic compounds if the technique is not accompanied by a supply of manure or compost to compensate for the deficit that could be created by the acceleration of processes of mineralization (Douamba et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les semences sont déposées dans les cuvettes de zaï à sec ou dès qu'elles ont assez d'eau. Les effets du zaï sur l'amélioration de la fertilité physique, chimique et biologique des sols, et sur les rendements des cultures ont été largement documentés (Roose, 2004 ;Zougmoré et al, 2004;Sawadogo et al, 2008;Hien et al, 2010;Doamba et al, 2011 ;Somé et al, 2015). D'autres structures plus ou moins pérennes de conservation des eaux et des sols ou de défense et restauration des sols sont parfois développées sur les parcelles : les cordons pierreux, les demi-lunes, les bandes enherbées (Figure 3 (Figure 3).…”
Section: Resultats Caractéristiques Des Systèmes De Cultureunclassified
“…Cependant, la qualité et la quantité de la matière organique apportée au sol affecte les microorganismes (Konaté et al, 2003 ;Doamba, 2009) responsables de la minéralisation et par conséquent, de la mise à disposition des nutriments aux cultures. Il est en effet reconnu que les microorganismes telluriques jouent un rôle déterminant dans le recyclage des éléments nutritifs, la facilitation des processus chimiques, et surtout dans l'amélioration des rendements (Konaté et al, 2003 ;Ouédraogo et al, 2004 ;Ouédraogo et al, 2005 ;Lavelle et al, 2006 ;Oberson et al, 2006 ;Chapuis-Lardy et al, 2009 ;Pey, 2010 ;Doamba et al, 2011 ;Zida et al, 2011 ;Traoré, 2012 ;Ouédraogo et al, 2014 a et b). En outre, la diversité des organismes du sol et la relation entre ces organismes, permettent d'améliorer la résilience du sol.…”
Section: Introductionunclassified